A Novel Octapeptide Derived From G Protein-Coupled Receptor 124 Improves Cognitive Function Via Pro-Angiogenesis In A Rat Model Of Chronic Cerebral Hypoperfusion-Induced Vascular Dementia - Xiao Y; Shen H; Li R; Zhou X; Xiao H; Yan J (Dove Medical Press, 2019)
Ying Xiao,1 Hong Shen,2 Rui Li,3 Xia Zhou,2 Hong Xiao,2 Jun Yan4 1College of Science, China Pharmaceutical University, Nanjing, People’s Republic of China; 2Neuro-Psychiatric Institute, Nanjing Medical University Affiliated Brain Hospital, Nanjing, People’s Republic of China; 3School of Pharmacy, Nanjing Medical University, Nanjing, Nanjing, People’s Republic of China; 4Department of Geriatric Neurology, Nanjing Medical University Affiliated Brain Hospital, Nanjing, People’s Republic of ChinaCorrespondence: Hong Shen; Hong XiaoNeuro-Psychiatric Institute, Nanjing Medical University Affiliated Brain Hospital, 264# Guangzhou Road, Nanjing 210029, People’s Republic of ChinaTel +86 25 8229 6334; +86 25 8229 6352Email shenhong_nbh@njmu.edu.cn; xhnkyy123@163.comPurpose: The lack of effective therapies mandates the development of new treatment strategies for vascular dementia (VaD). G protein-coupled receptor 124 (GPR124) may be a therapeutic target for angiogenesis-related diseases of CNS, including VaD. The GCPF peptide is a truncated and screened fragment of the GPR124 extracellular domain. The potential use of GCPF for VaD treatment, angiogenesis and targeting of integrin αvβ3 are evaluated.Methods and results: First, the in vivo results indicated that the GCPF peptide could decrease mean escape latency and increase platform crossing times in BCCAO rats. Second, the in vitro and ex vivo results indicated that the GCPF peptide was an active angiogenic peptide and could promote hCMEC/D3 cell migration and adhesion to ECM molecules. Third, in silico analyses predicted that GCPF could specifically interact with integrin αvβ3; the ∆G of GCPF binding to the binding pocket was −16.402 KJ/mol. The molecular characteristics indicated that highly hydrophilic GCPF with a pI of 11.70 had a short half-life in mammals (∼1 hr). Finally, the ELISA experiments indicated that low dissociation constant (Kd= 2.412±0.455 nM) corresponds to the high affinity of GCPF for integrin αvβ3.Conclusion: The data indicate that adhesion of GCPF immobilized on ECM surface to endothelial cells via integrin αvβ3 modulates cellular functions to promote angiogenesis and improve cognitive function. This is the first report to prove that GCPF, a novel octapeptide, may be an effective strategy for VaD therapy.Keywords: G-protein coupled receptor 124, vascular dementia, chronic cerebral hypoperfusion, angiogenesis, integrin, protein therapy